RASIO FREE FLOAT SAHAM ; SEBAGAI ANALISA TEKNIKAL DALAM PENGAMBILAN KEPUTUSAN BERINVESTASI STUDI KASUS PADA SAHAM LQ 45 PERIODE 2020-2022 - Neng Susi Susilawati Sugiana; Imas Purnamasari; Budi Purnomo (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Abstract Entering into stock investing activities is an exciting activity for investors in the hope of providing reserves in financial conditions that provide large nominal profits and instant timeframes. However, investors are required to dive deeper into knowledge both fundamentally and technically, regarding stock terms such as free float stocks, where free float shares will reflect the condition of the issuer who sells the shares. In this case using technical analysis to see the free float of stocks from LQ 45, reading history or portfolios of minority shares or remaining shares that can be sold to the regular market or for novice investors by analyzing the movement of stock trends from a stock report, can sort out free float efficient and inefficient stocks, so as to increase the accuracy of novice investors in making the right investment decisions. This type of research uses descriptive research and takes data on company shares listed on the LQ 45 index with 45 listed companies. The results showed that the free float performance of LQ 45 company stock was good based on stock returns and risk.